Bedaquiline Inhibits the ATP Synthase in Mycobacterium abscessus and Is Effective in Infected Zebrafish - Dupont, Christian (Antimicrob Agents Chemother, 2017)
Pulmonary infections caused by Mycobacterium abscessus are emerging as a global threat, especially in cystic fibrosis patients. Further intensifying the concern of M. abscessus infection is the recent evidence of human-to-human transmission of the infection. M. abscessus is a naturally multidrug-resistant fast-growing pathogen for which pharmacological options are limited. Repurposing antitubercular drugs represents an attractive option for the development of chemotherapeutic alternatives against M. abscessus infections. Bedaquiline (BDQ), an ATP synthase inhibitor, has recently been approved for the treatment of multidrug-resistant tuberculosis. Herein, we show that BDQ has a very low MIC against a vast panel of clinical isolates. Despite being bacteriostatic in vitro, BDQ was highly efficacious in a zebrafish model of M. abscessus infection. Remarkably, a very short period of treatment was sufficient to protect the infected larvae from M. abscessus-induced killing. This was corroborated with reduced numbers of abscesses and cords, considered to be major pathophysiological signs in infected zebrafish. Mode-of-action studies revealed that BDQ triggered a rapid depletion of ATP in M. abscessus in vitro, consistent with the drug targeting the F(o)F(1) ATP synthase. Importantly, despite a failure to select in vitro for spontaneous mutants that are highly resistant to BDQ, the transfer of single nucleotide polymorphisms leading to D29V or A64P substitutions in atpE conferred high resistance, thus resolving the target of BDQ in M. abscessus. Overall, this study indicates that BDQ is active against M. abscessus in vitro and in vivo and should be considered for clinical use against the difficult-to-manage M. abscessus pulmonary infections.